2022
DOI: 10.1177/19417381221078537
|View full text |Cite
|
Sign up to set email alerts
|

The Clinician’s Guide to Baseball Pitching Biomechanics

Abstract: Context: Improper baseball pitching biomechanics are associated with increased stresses on the throwing elbow and shoulder as well as an increased risk of injury. Evidence Acquisition: Previous studies quantifying pitching kinematics and kinetics were reviewed. Study Design: Clinical review. Level of Evidence: Level 5. Results: At the instant of lead foot contact, the elbow should be flexed approximately 90° with the shoulder at about 90° abduction, 20° horizontal abduction, and 45° external rotation. The stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 68 publications
0
16
0
Order By: Relevance
“…Other authors have suggested that pitchers may demonstrate suboptimal mechanics not only because of motor-learning and pattern development but also because physical factors such as range of motion, strength, and stability across the kinetic chain may limit an athlete's ability to achieve ideal positions. 6,7,9,10 Creating a systematic process for 2D-motion analysis of the pitching motion can improve communication between medical professionals and those involved in athlete development (coaches, performance staff). In doing so the multidisciplinary team may address physical factors limiting pitching performance, design comprehensive rehabilitation plans, and monitor mechanical compensations during return-to-throwing programs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other authors have suggested that pitchers may demonstrate suboptimal mechanics not only because of motor-learning and pattern development but also because physical factors such as range of motion, strength, and stability across the kinetic chain may limit an athlete's ability to achieve ideal positions. 6,7,9,10 Creating a systematic process for 2D-motion analysis of the pitching motion can improve communication between medical professionals and those involved in athlete development (coaches, performance staff). In doing so the multidisciplinary team may address physical factors limiting pitching performance, design comprehensive rehabilitation plans, and monitor mechanical compensations during return-to-throwing programs.…”
Section: Discussionmentioning
confidence: 99%
“…3 Commonly, the motion is broken down into six phases, interconnected by a series of kinematic events, beginning with windup and ending with ball release (Figure 1). 2,[4][5][6][7][8] Limitations in strength, range of motion, and suboptimal mechanics can affect each phase of the throwing motion. Physical and mechanical deficits can therefore place increased stress across the shoulder and elbow leading to elevated injury risk.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations